2022
DOI: 10.1111/jipb.13228
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signaling in plant responses to abiotic stresses

Abstract: Adverse variations of abiotic environmental cues that deviate from an optimal range impose stresses to plants. Abiotic stresses severely impede plant physiology and development. Consequently, such stresses dramatically reduce crop yield and negatively impact on ecosystem stability and composition. Physical components of abiotic stresses can be, for example, suboptimal temperature and osmotic perturbations, while representative chemical facets of abiotic stresses can be toxic ions or suboptimal nutrient availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 130 publications
(200 reference statements)
0
83
0
Order By: Relevance
“…Ca 2+ plays an important role in plant responses to cold stress and COR gene expression ( 1 ); however, it is unclear how Ca 2+ signal is relayed into cold signaling. CPKs have both Ca 2+ sensing and responding function ( 23 ). To examine the possibility that CPKs might transmit the cold-induced Ca 2+ signal, we conducted quantitative polymerase chain reaction (qPCR) to analyze the expression of CPK genes in a rapid response to cold stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ plays an important role in plant responses to cold stress and COR gene expression ( 1 ); however, it is unclear how Ca 2+ signal is relayed into cold signaling. CPKs have both Ca 2+ sensing and responding function ( 23 ). To examine the possibility that CPKs might transmit the cold-induced Ca 2+ signal, we conducted quantitative polymerase chain reaction (qPCR) to analyze the expression of CPK genes in a rapid response to cold stress.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ is a ubiquitous second messenger that triggers plant responses to cold stress in plants ( 1 ). There are some Ca 2+ sensor or Ca 2+ -related proteins such as CaMs, CBLs, CDPKs/CPKs, CRLKs, and CAMTAs in plants ( 23 ). CRLK1 has been reported to regulate plant freezing tolerance, and its activation is enhanced by CaM ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early signaling events, including cytosolic Ca 2+ influx and burst of ROS, can be activated within a very short time ( Baxter et al, 2014 ). The interconnection of Ca 2+ signaling with ROS production complicates the underlying mechanism under different abiotic stresses in plants, which are intimately correlated with diverse abiotic stresses ( Baxter et al, 2014 ; Dong et al, 2022 ). Previous data showed that Ca 2+ signal formation and H 2 O 2 accumulation are fine-tuned in a reciprocal manner ( Steinhorst and Kudla, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Responding to environmental stimuli with appropriate molecular mechanisms is essential to all life forms and particularly so in sessile organisms such as plants. To this end, plants have evolved both rapid early mechanisms such as the activation of channels and kinases directly or indirectly through protein sensors [ 1 , 2 , 3 , 4 , 5 , 6 ], as well as the slower systemic adaptive responses that include changes in their transcriptomes and proteomes [ 7 , 8 , 9 , 10 , 11 , 12 ]. To enable these processes and concomitantly tune their responses to the environment, complex cellular-signaling mechanisms have evolved, some of which have no homologues in animals [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Editorial On the Special Issue: New Horizons In Plant Cell S...mentioning
confidence: 99%